Impact of Interest Rate Hike on Financing Debt, Indonesian Government Toll Road Project - Azhar Eka Septiana; Neyla Mutiara Sabrina; Silvia Ananda Putri; Kayla Ardi Putri; Muhammad Fauzan Akbar Rafsanjani; Galuh Boga Guswara (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study analyzes the impact of rising interest rates on the sustainability of debt financing in Indonesian government toll road projects, using the Cisumdawu Toll Road project as a case study. Research Method: The study employed a quantitative case study approach, using financial feasibility analysis and scenario-based sensitivity analysis. Secondary data were obtained from Bank Indonesia benchmark interest rates (BI 7-Day Reverse Repo Rate), project financing structures, and toll road investment assumptions. Financial indicators used in the analysis included Cost of Debt, Weighted Average Cost of Capital (WACC), Debt Service Coverage Ratio (DSCR), Net Present Value (NPV), and Internal Rate of Return (IRR). Results and Discussion: The findings indicate that rising interest rates significantly increase borrowing costs and debt-servicing obligations, thereby reducing project cash-flow resilience and investment feasibility. Higher interest rates also weaken DSCR performance, increase WACC, and reduce NPV and IRR values. Implications: The study highlights the importance of stable monetary policy, effective governance of infrastructure financing, and government support mechanisms in maintaining the resilience of long-term infrastructure investment. Originality: Integrating interest rate sensitivity analysis with debt financing sustainability in the context of the Cisumdawu Toll Road project, which has rarely been discussed comprehensively in previous infrastructure financing studies in Indonesia.